Pengetahuan Mahasiswa tentang Aktivitas Fisik terhadap Resiko Penyakit Tidak Menular - Fahni Haris; Kellyana Irawati; Laili Nur Hidayati; Agnes Erida Wijayanti; Ignatius Djuniarto; Andri Purwandari; Sendhi Tristanti Puspitasari (Universitas Muhammadiyah Klaten, 2025)
Background: The incidence of non-communicable diseases (NCDs) is increasing globally. Physical exercise, as a preventive and management strategy for NCDs, should be introduced to students at an early stage. Assessing students' level of knowledge regarding physical activity in relation to NCDs is essential as an academic foundation for conducting health promotion in hospital or community settings. Objective: To assess students' knowledge of physical activity in mitigating the risk of NCDs. Methods: This study employs a quasi-experimental with one group pretest-posttest design. The sample consists of 20 active nursing students who will undergo a clinical practice phase. Results: The paired t-test indicate a significant difference in the mean scores before and after the material presentation (p = 0.001; p < 0.05). Statistically, students' knowledge scores regarding physical activity for individuals with NCDs increased by an average of 2.4 points compared to pre-test score. Conclusion: Providing educational material on physical activity for NCDs is highly recommended for nursing students preparing for clinical practice to enhance their knowledge